The Effect of Good Governance on Preventing Potential Fraud in the Management of BOK Funds at Puskesmas in Mojokerto District - Yoosita Aulia; Nurhayati Sofian; Alberta Esti (Jurnal Ilmiah Akuntansi, 2024)
This study aims to test and analyze the effect of good governance—specifically accountability, effectiveness, and transparency—on the potential for fraud in the management of BOK funds at Puskesmas (Health Centers) in Mojokerto District. A simple random sampling technique was employed, and samples were selected randomly based on the calculated sample size using the Slovin formula. The analysis was conducted using multiple linear regression to determine the relationships between the variables. The findings reveal that accountability, effectiveness, and transparency do not significantly influence the potential for fraud at the Mojokerto Regency Health Centers. This suggests that the implementation of good governance practices does not directly impact the potential for fraudulent activities in the management of BOK funds at these health centers. These results highlight the need for further investigation into other factors that may contribute to fraud prevention and underscore the complexity of fraud management within public health institutions.